Comparative Analysis of Coronal Sealing Materials in Endodontics: Exploring Non-Eugenol Zinc Oxide-Based versus Glass-Ionomer Cement Systems - Alamin, Mohamed Hashim; Yaghi, Sara Ayman; Al-Safi, Abdullah Faris; Bouresly, Wared R. Y. R.; Fakhruddin, Kausar Sadia; Samaranayake, Lakshman Perera; Al Shehadat, Saaid (European Journal of Dentistry, 2024)
The proper closure of the access cavity between appointments during endodontic treatment is paramount and relies on temporary fillings. This systematic review evaluates the effectiveness of zinc oxide-based materials and glass-ionomer cement (GIC) as temporary coronal sealers after root canal treatment in extracted human teeth. Three databases were searched to identify randomized clinical trials that examined the sealing properties of various temporary sealing materials using dyes or stains as indicators. A total of seven in vitro studies that fulfilled the eligibility criteria were critically analyzed. These indicated significant variations in the relative sealing ability of the coronal breach of endodontically treated teeth, either by zinc oxide or GIC-based materials. While GIC-based material (e.g., Fuji IX and Fuji II) exhibited superior sealing of single-rooted teeth, zinc oxide-based material (e.g., Cavit, Coltosol, Caviton) also showed promising attributes. Resin-modified GIC formulations displayed enhanced physical properties, yet challenges related to adhesive failure and shrinkage during polymerization were observed. Zinc oxide-based materials have demonstrated superior coronal sealing effectiveness over certain GIC in controlled settings. Their premixed nature ensures consistent application and hygroscopic properties improve cavity sealing. However, the focus on dye penetration tests for microleakage in vitro may not fully represent the risk of bacterial infiltration. Thus, in vivo studies are crucial for validating these findings in clinical contexts.
Keywords: temporary coronal sealers; sealing properties; microleakage; glass-ionomer cement; zinc oxide-based materials; root canal treatment